Subclavian artery laceration following clavicle fracture, successfully treated with a combined endovascular and open surgical approach. Issue 7 (2nd July 2021) - Arnold, Samuel; Gilroy, Darina; Laws, Peter; Kempthorne, Josh
Abstract : Subclavian artery injury is a rare complication of clavicle fracture. The fractured clavicle can lacerate the underlying subclavian artery. Life-threatening haemorrhage can occur secondary to arterial laceration, and if distal blood flow is impaired, upper limb ischaemia can develop. There is little discussion in the literature regarding combined (or 'hybrid') endovascular and open surgical management of acute subclavian injuries secondary to clavicle fracture. We report a case of subclavian artery laceration secondary to clavicle fracture, managed with a combined endovascular and open surgical approach. An endovascular balloon was used for proximal arterial control, while surgical exposure and primary repair of the subclavian artery was completed, followed by fixation of the clavicle. There was no sustained vascular or neurological impairment at follow-up. We suggest that select traumatic injuries of the subclavian artery can be safely and successfully managed with a combined endovascular and open surgical approach.